Luteal phase support in assisted reproductive technology treatment: focus on Endometrin® (progesterone) vaginal insert - Jerome H Check (Dove Medical Press, 2009)
Jerome H CheckThe University of Medicine and Dentistry of New Jersey, Robert Wood Johnson Medical School at Camden, Cooper Hospital/University Medical Center, Department of Obstetrics and Gynecology, Division of Reproductive Endocrinology and Infertility, Camden, New Jersey, USAAbstract: Supplementation of progesterone in the luteal phase and continuance of progesterone therapy during the first trimester has been found in several studies to have benefits in promoting fertility, preventing miscarriages and even preventing pre-term labor. Though it can be administered orally, intramuscularly or even sublingually, a very effective route with fewer side effects can be achieved by an intravaginal route. The first vaginal preparations were not made commercially but were compounded by pharmacies. This had the disadvantage of lack of control by the Food and Drug Administration (FDA) ensuring efficacy of the preparations. Furthermore there was a lack of precise dosing leading to batch to batch variation. The first commercially approved vaginal progesterone preparation in the United States was a vaginal gel which has proven very effective. The main side effect was accumulation of a buildup of the vaginal gel sometimes leading to irritation. Natural micronized progesterone for vaginal administration with the brand name of Utrogestan A® had been approved even before the gel in certain European countries. Endometrin® vaginal tablets are the newest natural progesterone approved by the FDA. Comparisons to the vaginal gel and to intramuscular progesterone have shown similar efficacy especially in studies following controlled ovarian hyperstimulation and oocyte egg retrieval and embryo transfer. Larger studies are needed to compare side effects.Keywords: progesterone vaginal tablets, luteal phase, miscarriage, pregnancy rates